International physical therapists consensus on clinical descriptors for diagnosing rotator cuff related shoulder pain: A Delphi study - Requejo-Salinas N. (2022)
© 2022 Associação Brasileira de Pesquisa e Pós-Graduação em FisioterapiaBackground: There is a lack of standardized criteria for diagnosing rotator cuff related shoulder pain (RCRSP). Objective: To identify the most relevant clinical descriptors for diagnosing RCRSP. Methods: A Delphi study was conducted through use of an international physical therapists expert panel. A 3-round Delphi survey involving an international panel of physical therapists experts with extensive clinical, teaching, and research experience was conducted. A search query was performed in Web of Science, along with a manual search, to find the experts. The first round was composed of items obtained from a previous pilot Delphi study along with new items proposed by the experts. Participants were asked to rate items across six clinical domains using a five-point Likert scale. An Aiken's Validity Index ≥ 0.7 was considered indicative of group consensus. Results: Fifteen experts participated in the Delphi survey. After the three rounds, consensus was reached on 18 clinical descriptors: 10 items were included in the “subjective examination” domain, 1 item was included in the “patient-reported outcome measures” domain, 3 items in the “diagnostic examination” domain, 2 items in the “physical examination” domain”, and 2 items in the “functional tests” domain. No items reached consensus within the “special tests” domain. The reproduction of symptoms in relation to the application of load, the performance of overhead activities, and the need of active and resisted movement assessment were some of the results with greatest consensus. Conclusion: In this Delphi study, a total of 18 clinical descriptors across six clinical domains were agreed upon for diagnosing RCRSP.